Lagoa Santa's contribution to the origins and life of early Americans. Issue 3 (30th May 2018) - Da‐Gloria, Pedro; Hubbe, Mark; Neves, Walter A.
Abstract: The region of Lagoa Santa, Central‐Eastern Brazil, provides an exceptional archeological record about Late Pleistocene/Early Holocene occupation of the Americas. Since the first interventions made by the Danish naturalist Peter Lund in the 19th century, hundreds of human skeletons have been exhumed in the region. These skeletons are complemented by a rich botanic, faunal, technological, and geomorphological archeological record. We explore here the contributions of Lagoa Santa material to the origins and lifestyle of early Americans, providing an historic background. Cranial morphology of Lagoa Santa skeletons allowed the proposition of a model of two biological components for the occupation of the Americas, in which early Americans are morphologically similar to people of African and Australo‐Melanesian origin. Furthermore, the archeological record in the region has revealed an intense use of plant resources, a restricted spatial distribution, and the symbolic elaboration of local hunter‐gatherers, unveiling a distinct lifestyle compared to early North American populations.